Body studies the basics - Richardson, Niall; Locks, Adam (Routledge, 2014)
"Consideration of the body as a subject for study has increased in recent years with new technologies, forms of modification, debates about obesity and issues of age being brought into focus by the media. Drawing on contemporary culture, Body Studies: The Basics introduces readers to the key concerns and debates surrounding the study of the sociological body, cutting across disciplines to cover topics which include:Nature vs. Culture: how we 'build' and transform our bodiesConformity and resistance in bodily practice Issues of body image...beauty, diet, exercise and ageSporting bodies and the pursuit of idealsEnfreakment, disability and monstrosityCyborgs and virtual online bodiesWith further reading signposted throughout, this accessible book is essential reading for anyone studying the body through the lens of sociology, cultural studies, sports studies, media studies and gender studies; and all those with an interest in how the physical body can be a social construct"..
Keywords: SOCIAL SCIENCE / Sociology / General; Gesellschaft; Human body -- Social aspects; Soziologie; Körper